The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1002/mnfr.201300806
|View full text |Cite
|
Sign up to set email alerts
|

Estrogen receptor beta is involved in skeletal muscle hypertrophy induced by the phytoecdysteroid ecdysterone

Abstract: These findings provide new therapeutic perspectives for the treatment of muscle injuries, sarcopenia, and cachectic disease, but also imply that such a substance could be abused for doping purposes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
89
0
14

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 83 publications
(108 citation statements)
references
References 32 publications
(45 reference statements)
5
89
0
14
Order By: Relevance
“…As further components of the insect meal, which may have contributed to its metabolic effects, ecdysteroids come into question. Ecdysteroids from which 20‐hydroxyecdysone is the quantitatively main in Tenebrio molitor larvae generally control molting (ecdysis) and metamorphosis in insects and have been reported to exert interesting metabolic actions including anti‐obesity and hypoglycemic effects and hypertrophic effects on muscle in mammals . We are not aware of any literature data on ecdysteroid concentrations in Tenebrio molitor larvae meal, but the concentration of 20‐hydroxyecdysone in the hemolymph of Tenebrio molitor larvae was reported to be in the range between 50 and 1500 ng mL –1 depending on the developmental stage of larvae (the peak level is found in larvae of eyestage 12).…”
Section: Discussionmentioning
confidence: 98%
“…As further components of the insect meal, which may have contributed to its metabolic effects, ecdysteroids come into question. Ecdysteroids from which 20‐hydroxyecdysone is the quantitatively main in Tenebrio molitor larvae generally control molting (ecdysis) and metamorphosis in insects and have been reported to exert interesting metabolic actions including anti‐obesity and hypoglycemic effects and hypertrophic effects on muscle in mammals . We are not aware of any literature data on ecdysteroid concentrations in Tenebrio molitor larvae meal, but the concentration of 20‐hydroxyecdysone in the hemolymph of Tenebrio molitor larvae was reported to be in the range between 50 and 1500 ng mL –1 depending on the developmental stage of larvae (the peak level is found in larvae of eyestage 12).…”
Section: Discussionmentioning
confidence: 98%
“…In spite of more than 40 years of research, the mechanism of action of these molecules on mammals/humans has not been elucidated, as only diverging reports are available for the moment. Several data favour an action on membranes through a GPCR receptor (17), whereas other ones suggest the involvement of a nuclear receptor, the estrogen receptor ERβ (18,19).…”
Section: How Do Ecdysteroids Work?mentioning
confidence: 99%
“…There is in fact no direct evidence for the binding of 20E to nuclear estrogen (or androgen) receptors (12,13). The evidence of ERβ involvement in 20E effect is based on the use of specific pharmacological activators or inhibitors of ERs, the former being able to mimic and the latter to inhibit the effects of 20E on target cells such as osteoblasts (20) or myoblasts (19). These studies however do not bring proofs for a direct 20E binding, as ER receptor could be activated indirectly, and even in the absence of ligand, e.g.…”
Section: How Do Ecdysteroids Work?mentioning
confidence: 99%
“…It is essential for moulting and reproduction in many arthropod species, and is also present as an insecticide in some plant species where it disrupts the development of insect pests that would feed upon them . Reports in the older steroid literature have suggested that ecdysteroids may exert a small anabolic effect in several mammal species, although more recent studies offer conflicting reports of their anabolic effects . Nonetheless, 20‐hydroxyecdysone has been found in dietary supplements such as Oxybolin 250 (High‐Tech Pharmaceuticals) and Ecdy‐Bolin (Truly Huge Supplements).…”
Section: ‐Hydroxyecdysone (2β3β14α20β22α25‐hexahydroxy‐5β‐cholmentioning
confidence: 51%